Penerapan Sistem Electronic Traffic Law Enforcement (ETLE) dalam Menurunkan Tingkat Pelanggaran Lalu Lintas di Kota Serang - Adelia Nur Azzani; Qotrun Nida (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This study aims to examine one of the efforts in creating order and safety on the highway by implementing the Electronic Traffic Law Enforcement (ETLE) system as an alternative to electronic traffic violation enforcement, without direct interaction between officers and violators and to find out how the ETLE system is implemented in Serang City and to what extent its effectiveness in reducing the number of traffic violations. The research method used is a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the implementation of ETLE in Serang City has been running quite well, supported by surveillance camera technology and an integrated reporting system. However, there are still obstacles such as the lack of public understanding of this system and the limited coverage of the ETLE monitoring area. The implementation of ETLE is a progressive step in traffic law enforcement, but it needs to be accompanied by more massive socialization and development of supporting infrastructure so that the results achieved are more optimal.